2014
DOI: 10.1111/avj.12269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an immunomodulatory feed additive on markers of immunity in pasture‐fed dairy cows

Abstract: The immunomodulatory effects of the additive observed in the current study and the associated enhanced neutrophil function demonstrated by other studies suggest a role in decreasing the rates of mastitis and other infectious diseases of dairy cattle, particularly during times of nutritional or physiological stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…We previously reported that one of the most widely used immunomodulatory feed supplements, YCA, decreased mammary infections in dairy cows and improved milk production, 4 and improved innate and adaptive immune responses function in immune-challenged ruminant livestock. [1][2][3][4][5][6] This study closes an important gap in our knowledge, as it helps to explain the improved innate and adaptive immune responses reported in ruminant livestock fed YCA. At the same time, we want to caution the reader, as gene expression may or may not translate into changes on the protein level and/or functional changes like our previously observed TCA-induced changes in L-selectin gene and protein expression across various ruminant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that one of the most widely used immunomodulatory feed supplements, YCA, decreased mammary infections in dairy cows and improved milk production, 4 and improved innate and adaptive immune responses function in immune-challenged ruminant livestock. [1][2][3][4][5][6] This study closes an important gap in our knowledge, as it helps to explain the improved innate and adaptive immune responses reported in ruminant livestock fed YCA. At the same time, we want to caution the reader, as gene expression may or may not translate into changes on the protein level and/or functional changes like our previously observed TCA-induced changes in L-selectin gene and protein expression across various ruminant species.…”
Section: Discussionmentioning
confidence: 99%
“…We documented in several studies that feeding a yeast-containing additive (YCA; OmniGen-AF; Prince Agri Products, Inc., Quincy, IL, USA) at the recommended inclusion rate (0.25-0.50 wt% of diet) promotes immune function and maintains health and production in immune-or stress-challenged ruminant species and rodent models. [1][2][3][4][5][6] For example, Holstein heifers supplemented for 30 d with YCA had significantly increased surface-bound and internalized Escherichia coli in neutrophils. 5 Feeding YCA to the same animals tended to increase binding and uptake of Staphylococcus aureus by neutrophils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A placebo‐controlled study conducted in a small pasture‐based commercial dairy herd investigated the effects of a feed supplement containing hydrated aluminium silicate, silicon dioxide and yeast extract on the expression of the immune markers that are active against bacterial infections 3. Supplements were mixed with liquid molasses and water and then added to the grain.…”
Section: Production Animalsmentioning
confidence: 99%
“…A placebo-controlled study conducted in a small pasture-based commercial dairy herd investigated the effects of a feed supplement containing hydrated aluminium silicate, silicon dioxide and yeast extract on the expression of the immune markers that are active against bacterial infections. 3 Supplements were mixed with liquid molasses and water and then added to the grain. Concentrations of mRNA for L-selectin and interleukin-8R were significantly higher in the treatment group than in controls at day 60, the final day of supplementation; however, they decreased slightly after that.…”
mentioning
confidence: 99%